IMPACT OF HALAL CERTIFICATION ON THE PERFORMANCE OF FOOD SMALL MEDIUM ENTERPRISES - Giyanti, Ida; Indriastiningsih, Erna (Jurnal Ilmiah Teknik Industri, 2019)
The purpose of this paper is to analyze the impact of halal certification on the performance of food small-medium enterprises (SMEs). Specifically, this research aims to prove empirically whether there are significant differences in (1) profit margin of SMEs before and after obtaining a halal certificate; (2) profit margin between halal certified and non-certified SMEs; and (3) operational performance between halal certified and non-certified SMEs. Operational performance measures used in this study include production capacity, product quality, sales, net profit, amount of customers, customers' loyalty, and market share. A survey was conducted in 85 food SMEs in Surakarta city. Administered questionnaires were used to collect primary data from SMEs' managers. The differences regarding profit margin were analyzed using paired sample t-test and independent sample t-test. We determined the operational performance differences through non-parametric tests, namely the Mann Whitney U-test. Results based on objective data showed that there was no significant difference in the profit margin of SMEs before and after obtaining a halal certificate as well as between halal certified and non-certified SMEs. Results based on mean rank differences of subjective data of performance using the Mann Whitney U test showed that there were significant differences concerning all performance measures between halal certified and non-certified SMEs.